Carbon fibers decorated with TiO2 nanoparticles for photocatalytic degradation of methylene blue dye - Kumar Chennam, Pavan; Sepúlveda, Marcela; Rihova, Martina; Alijani, Mahnaz; Kachlík, Martin; Zazpe, Raul; Pavlinak, David; Maca, Karel; Macak, Jan M. (Frontiers in Nanotechnology, 2024)
This report demonstrates the development of carbon fibers (CFs) decorated with TiO2 nanoparticles (NPs) as an efficient photocatalyst for the photocatalytic degradation of methylene blue (MB) as a model dye. Carbon fibers were produced by carbonization of polyacrylonitrile fibers, previously produced by centrifugal spinning. Subsequently, the CFs were decorated with TiO2 NPs (CFs@TiO2) by tailored soaking protocol using aqueous TiCl4 solution with different concentrations (0.025, 0.05, 0.1, and 0.2 M). SEM analyses revealed that soaking in TiCl4 produced a smooth, conformal, continuous TiO2 nanoparticulate coating with thickness increasing from 40.4 ± 21.2 to 257.9 ± 63.9 nm with increasing TiCl4 concentration. X-ray diffraction and Raman spectroscopy confirmed the anatase nature of TiO2. Photocatalytic decomposition rates of MB were assessed under UV light illumination for all CFs@TiO2 samples, and it was revealed that the lowest amount of TiO2 NP on C yielded the highest rates. The synergistic interaction between CFs and TiO2 NPs with a uniform morphology and a well-crystalline anatase structure, present in an optimal amount of fiber bodies, is the key reason for the remarkable photocatalytic performance. This work shows that C fibers decorated with an optimal amount of TiO2 NPs have a great potential as an effective photocatalytic material.